(untitled) (Advances in Applied Mathematics and Mechanics, 2018)
In the present work concentrated on the two-dimensional problem of generalized thermoelasticity for a fiber-reinforced anisotropic thick plate under initial stress. Using generalized thermoelasticity theory with fractional order heat conduction, the problem has been solved by a normal mode analysis. The effect of hydrostatic initial stresses and fractional order parameter is shown graphically on the distributions of the temperature, displacement and thermal stress components. It is found from the graphs that the initial stress and the fractional parameter significantly influence the varieties of field amounts.